Fetofetal Transfusion Syndrome in Monochorionic-Triamniotic Triplets Treated with Fetoscopic Laser Ablation: Report of Two Cases and A Systematic Review - Blumenfeld, Yair J.; Shamshirsaz, Alireza A.; Belfort, Michael A.; Hintz, Susan R.; Moaddab, Amirhossein; Ness, Amen; Chueh, Jane; El-Sayed, Yasser Y.; Ruano, Rodrigo (American Journal of Perinatology Reports, 2015)
Objective This study aims to determine the clinical outcomes of monochorionic-triamniotic (MT) pregnancies complicated by severe fetofetal transfusion undergoing laser photocoagulation.Study Design We report two cases of MT triplets complicated by fetofetal transfusion syndrome (FFTS) and a systematic review classifying cases into different subtypes: MT with two donors and one recipient, MT with one donor and two recipients, MT with one donor, one recipient, and one unaffected triplet. The number of neonatal survivors was analyzed based on this classification as well as Quintero staging.Results A total of 26 cases of MT triples complicated by FFTS were analyzed. In 56% of the cases, the FFTS involved all three triplets, 50% of whom had an additional donor and 50% an additional recipient. Among the 24 cases that survived beyond 1 week after the procedure, the average gestational age of delivery was 29.6 weeks, and the average interval from procedure to delivery was 10.1 weeks. The overall neonatal survival rate was 71.7%, with demises occurring equally between donor and recipient triplets. Overall neonatal survival including survival of at least two fetuses occurred with equal frequency between the different groups.Conclusion Significant neonatal survival can be achieved in most cases of MT triplets with FFTS.
Keywords: fetofetal transfusion; monochorionic; triplets; laser; photocoagulation